The politics of water conflict conflict resolution mechanisms of Barangay water and sanitation associations (BWSAs) in Santa Barbara, Iloilo. - Calves, John Mark C.
In an era of scarcity and volatile seasonality, water conflict is a pressing challenge. Among the numerous Barangay Water and Santation Associations (BWSAs), which are unregulated community-based organizations providing domestic water, conflict resolution mechanisms are key components of how they govern. This research describes the water conflicts experienced, the conflict resolution and proactive mechanisms used in four rural communities. It explores the relationship of water system level with the types of conflicts and conflict management, and member?s attributes and their tendency to complain. It also probes the conflict resolution?s effect on member dynamics, BWSA rules and prevention of future conflicts. Four BWSAs, two each for Level I and III water system, were purposively selected in Santa Barbara, Iloilo. Three methods were used: organizational document analysis, key informant interviews with barangay captains and focus-group discussions with 9-10 members, in which male-female ratio is equal in most cases. The results show that water conflicts are more evident in Level III than in Level I water system, with water scarcity as a common problem. Conflicts are settled informally (e.g. community dialogues) in Level I while formally (e.g. barangay assembly, council sessions) in Level III. Overall, the respondents reported satisfaction on the effects of conflict management.